Cardiovascular Damage in COVID-19: Therapeutic Approaches Targeting the Renin-Angiotensin-Aldosterone System - Lumpuy-Castillo, Jairo (Int J Mol Sci, 2020)
Coronavirus disease 2019 (COVID-19) is usually more severe and associated with worst outcomes in individuals with pre-existing cardiovascular pathologies, including hypertension or atherothrombosis. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can differentially infect multiple tissues (i.e., lung, vessel, heart, liver) in different stages of disease, and in an age- and sex-dependent manner. In particular, cardiovascular (CV) cells (e.g., endothelial cells, cardiomyocytes) could be directly infected and indirectly disturbed by systemic alterations, leading to hyperinflammatory, apoptotic, thrombotic, and vasoconstrictive responses. Until now, hundreds of clinical trials are testing antivirals and immunomodulators to decrease SARS-CoV-2 infection or related systemic anomalies. However, new therapies targeting the CV system might reduce the severity and lethality of disease. In this line, activation of the non-canonical pathway of the renin-angiotensin-aldosterone system (RAAS) could improve CV homeostasis under COVID-19. In particular, treatments with angiotensin-converting enzyme inhibitors (ACEi) and angiotensin-receptor blockers (ARB) may help to reduce hyperinflammation and viral propagation, while infusion of soluble ACE2 may trap plasma viral particles and increase cardioprotective Ang-(1–9) and Ang-(1–7) peptides. The association of specific ACE2 polymorphisms with increased susceptibility of infection and related CV pathologies suggests potential genetic therapies. Moreover, specific agonists of Ang-(1–7) receptor could counter-regulate the hypertensive, hyperinflammatory, and hypercoagulable responses. Interestingly, sex hormones could also regulate all these RAAS components. Therefore, while waiting for an efficient vaccine, we suggest further investigations on the non-canonical RAAS pathway to reduce cardiovascular damage and mortality in COVID-19 patients.